High carbohydrate antigen 19–9 levels indicate poor prognosis in patients with bladder cancer following radical cystectomy - So, Sang Won; Han, Jang Hee; Yuk, Hyeong Dong; Jeong, Chang Wook; Kwak, Cheol; Ku, Ja Hyeon; Jeong, Seung-hwan (Frontiers in Oncology, 2025)
IntroductionOur team previously reported that elevated carbohydrate antigen (CA) 19–9 levels are associated with a worse prognosis in upper tract urothelial carcinoma (UTUC). Several studies have reported a correlation between high tumor burden and elevated CA19–9 levels in urothelial carcinomas. However, no studies have specifically examined the association between CA19–9 levels and outcomes of patients with bladder cancer who underwent radical cystectomy. Therefore, we aimed to evaluate the relationship of CA19–9 levels in bladder cancer patients following radical cystectomy.Materials and MethodsAmong the 984 patients who underwent radical cystectomy at the Seoul National University Hospital between 1991 and 2022, 564 patients had available preoperative CA19–9 levels. The patients were divided into two groups: a low CA19–9 group (CA19-9 ≤ 37 U/mL) and high CA19–9 group (CA19-9 > 37 U/mL). Demographic parameters as well as preoperative and postoperative findings were compared between these two groups. Recurrence-free survival and overall survival were analyzed using multivariate Cox regression and Kaplan-Meier analyses.ResultsSex distribution, age, body mass index, and underlying diseases (hypertension and diabetes mellitus) were similar between the two groups. The clinical T and N stages were significantly higher in the high CA19–9 group (P = 0.028 and P = 0.019, respectively). The operative procedures, including open, laparoscopic, and robotic surgeries, were similarly performed in both groups. Pathologic T and N stages also tended to be higher in the high CA19–9 group (P < 0.001 and P = 0.005, respectively). In the multivariate Cox regression analysis, the recurrence risk in the high CA19–9 group was significantly higher than that in the low group (HR 1.646; 95% CI 0.070–2.533, P = 0.023). The 5-year recurrence-free survival rate was 53.5% and 35.5% in the low and high CA19–9 groups, respectively (P < 0.001). Overall survival tended to be worse in the high CA19–9 group; however, this difference was not statistically significant.ConclusionsA high CA19–9 level is associated with a higher tumor burden in patients with bladder cancer. Furthermore, high CA19–9 levels are correlated to higher pathologic T and N stages after radical cystectomy and worse recurrence-free survival.